First record of Sergestes belonging to edwardsii species group (Sergestidae, Crustacea) from the Indian Ocean - Yousuf, Farzana; Kazmi, Quddusi B. (Zootaxa, 2005)
Sergestes edwardsii Kröyer, 1855 species group is composed of 9 species: S. semissis  (Burkenroad, 1940);  S. gibbilobatus (Judkins, 1978);  S. orientalis (Hansen, 1919);  S. geminus (Judkins, 1978);  S. tantillus (Burkenroad, 1940); S. consobrinus (Milne, 1968) California Current Form;  S. consobrinus (Milne, 1968) Central Form; S. edwardsii (Kröyer, 1855); S. brevispinatus (Judkins,1978).  The bathypelagic  shrimps  belonging  to  the  genus Sergestes  are  being studied from the  IIOE  material  for  its  taxonomy  and distribution.  Two species, S. brevispinatus (Judkins,1978) and  S. edwardsii (Kröyer, 1855), have been collected by the research vessels  ANTON BRUNN, ARGO, DIAMANTINA, METEOR, OSHORO MARU and VARUNA in the Indian Ocean for the first time.  Sergestes edwardsii is broadly distributed throughout the tropical Atlantic; it occurs from the New Land Plaza, Canada, to the wide of the Great Power of the North; throughout the Caribbean and Gulf of Mexico. Records at high northern latitudes in the Western Atlantic are probably due to transport by the Gulf Stream (Judkins, 1978). In Brazil it occurs in Para, in the Archipelago of Are Peter and Sao Paulo, Great River of North Fermando De Noronho  (D’Incao, F., 1995, 1998). Specimens of the present material are housed in the Marine Reference Collection and Resource Centre (MRC&RC), University of Karachi.